Green AI: Navigating sustainability and environmental impact from an Indian perspective - Martin Natasha; Sharma Vishnu (E3S Web of Conferences)
In the 21st century, where scientific advancements have empowered us to conquer the globe, artificial intelligence (AI) emerges as the technological marvel of the era. With the passage of time, AI has evolved from a tool executing pre-configured algorithmic codes to a more advanced version, possessing cognitive skills almost similar to humans. Today concerns are being raised regarding the environmental sustainability of AI. While the quantum of electricity utilised in running data mining centres, gallons of water used in counteracting the heat generated in data mining process and the inequitable distribution of such environmental losses across countries portray AI as an environmentally unviable option, its application in varied fields including agriculture, disaster management, energy management, emission control among others, exemplifies its instrumental role in fostering environmental sustainability. AI’s role in promoting environmental sustainability also attains crucial significance at a juncture when the global community is suffering disastrous ramifications of climate change, and the developmental needs of the global south are rising at a meteoric pace. The present study shall be focused on analysing AI-related developments taking place in Western countries and exploring ways in which AI applications can be introduced in India in an environmentally sustainable manner.